Distance learning technology, current instruction, and the future of education : Applications of today, practices of tomorrow - Song, Holim (Hershey, PA : Information Science Reference, 2010)
"The aim of this book is to explore current state and future direction of distance education from different research fields, reports and discussions from students, faculty members, researchers, and practitioners in the field of distance education, training development, and performance improvement" - Provided by publisher.
Includes bibliogr. references and index.
Keywords: Distance education -- Computer-assisted instruction; Educational technology